Afromontane small mammals do not follow the hump-shaped rule: altitudinal variation in the Soutpansberg Mountains, South Africa. (8th December 2014) - Taylor, Peter John; Munyai, Aubrey; Gaigher, Ian; Baxter, Rod
Abstract: Altitudinal transects of biodiversity are important to understanding macro-ecological patterns. Hump-shaped altitudinal profiles in species richness are a common pattern in terrestrial small-mammal communities studied previously mostly in New World mountain ranges. Based on capture–mark–recapture live-trapping conducted over four seasons (four nights per session) along an altitudinal transect from 1000 to 1747 m asl on the southern slopes of the Soutpansberg Mountains of northern South Africa, we recorded 12 species of small mammal, including nine rodents, two shrews and one elephant shrew (sengi). Three species of rodent and the sengi dominated the communities whilst six species were recorded with three or fewer captures. Although we found no effect of season, we found a significant linear increase in terrestrial small-mammal richness (but not Simpson's diversity, D) with altitude in the Soutpansberg Mountains located just north of the Tropic of Capricorn in South Africa. This trend could best be explained by an increase in the proportion of rocky cover and a change in vegetation from savanna to grassland. Peak densities of three common rodent species and one common insectivore varied from 10 ha −1 ( Elephantulus myurus ) to 54 ha −1 ( Micaelamys namaquensis ) and density showed no significant variation with season. However, density either declined ( Aethomys ineptus ) or increased ( Rhabdomys dilectus and Elephantulus myurus ) significantly with altitude; this variation was best explained by the proportion of rocky cover. Seasonal variation had a significant effect on body mass of two rodent species. A review of small-mammal studies from major mountain ranges in Africa and Madagascar found that the hump-shaped pattern is not common. Declines in richness with increasing altitude as well as cases of no significant altitudinal change were the most common patterns noted. Tropical African mountains (including the Soutpansberg with 27 species) have far higher small-mammal diversity than temperate African mountains.